Pogodba o komunalnem opremljanju - Delić Kamenčić, Ermina (Pravni letopis, 2023)
The first part of the paper briefly introduces the retrofitting of building land and explains that the provision of the utility equipment to building land is one of the essential conditions for construction. It also explains in which cases it is possible to start construction on un-equipped building land. The second part of the paper focuses on the communal utilities contract, whereby the investor and the municipality agree that the investor, instead of the municipality, will build (part of ) the communal utilities to equip the land on which the investor intends to build, and then hand it over to the municipality free of charge. This article presents the subject matter of the contract, the mandatory content of the communal utilities contract and the handover of the constructed utility equipment to the municipality. The third part of the paper highlights selected practical issues. The paper presents the issues related to obtaining the right to build (of the utility equipment) and its transfer to the municipality, obtaining the building and use permit, coordinating the time schedule between the contractual parties and setting the time limit for the construction of the utility equipment.
Keywords: gradbeno dovoljenje; komunalna opremljenost; občina; pogodbe; stavbna zemljišča; uporabno dovoljenje